Dickkopf‐1‐promoted vasculogenic mimicry in non‐small cell lung cancer is associated with EMT and development of a cancer stem‐like cell phenotype. Issue 9 (31st May 2016) - Yao, Lingli; Zhang, Danfang; Zhao, Xiulan; Sun, Baocun; Liu, Yanrong; Gu, Qiang; Zhang, Yanhui; Zhao, Xueming; Che, Na; Zheng, Yanjun; Liu, Fang; Wang, Yong; et al.
Abstract: To characterize the contributions of Dickkopf‐1 (DKK1) towards the induction of vasculogenic mimicry (VM) in non‐small cell lung cancer (NSCLC), we evaluated cohorts of primary tumours, performed in vitro functional studies and generated xenograft mouse models. Vasculogenic mimicry was observed in 28 of 205 NSCLC tumours, while DKK1 was detected in 133 cases. Notably, DKK1 was positively associated with VM. Statistical analysis showed that VM and DKK1 were both related to aggressive clinical course and thus were indicators of a poor prognosis. Moreover, expression of epithelial‐mesenchymal transition (EMT)‐related proteins (vimentin, Slug, and Twist), cancer stem‐like cell (CSC)‐related proteins (nestin and CD44), VM‐related proteins (MMP2, MMP9, and vascular endothelial‐cadherin), and β‐catenin‐nu were all elevated in VM‐positive and DKK1‐positive tumours, whereas the epithelial marker (E‐cadherin) was reduced in the VM‐positive and DKK1‐positive groups. Non‐small cell lung cancer cell lines with overexpressed or silenced DKK1 highlighted its role in the restoration of mesenchymal phenotypes and development of CSC characteristics. Moreover, DKK1 significantly promotes NSCLC tumour cells to migrate, invade and proliferate. In vivo animal studies demonstrated that DKK1 enhances the growth of transplanted human tumours cells, as well as increased VM formation, mesenthymal phenotypes and CSC properties. Our results suggest that DKK1 can promote VM formation via induction of the expression of EMT and CSC‐related proteins. As such, we feel that DKK1 may represent a novel target of NSCLC therapy.